3D Flower-Like NiO Hierarchical Structures Assembled With Size-Controllable 1D Blocking Units: Gas Sensing Performances Towards Acetylene - Zhang, He; Chen, Wei-Gen; Li, Yan-Qiong; Jin, Ling-Feng; Cui, Fang; Song, Zi-Hao (Frontiers in Chemistry, 2018)
Acetylene gas (C2H2) is one of the main arc discharge characteristic gases dissolved in power transformer oil. It is of great potential to monitor the fault gas on-line by applying gas sensor technology. In this paper, gas sensors based on nanorods and nanoneedles assembled hierarchical NiO structures have been prepared. Herein, we focus on investigate the relationship between the sizes of the assembling blocking units and gas sensing properties. It can be found that the addition of CTAB/EG plays a vital role in controlling the sizes of blocking unit and assembly manner of 3D hierarchical structures. A comparison study reveals that an enhanced gas sensing performance toward C2H2 for the sensor based on nanoneedle-assembled NiO flowers occurs over that of nanorod-assembled NiO. This enhancement could be ascribed to the larger specific area of needle-flower, which provides more adsorption and desorption sites for chemical reaction as well as effective diffusion channels for C2H2. Besides, a method of calculating the specific surface area without BET testing was presented to verify the results of gas sensing measurement. The possible growth mechanism and gas sensing mechanism were discussed. Such a synthesis way may open up an avenue to tailor the morphologies and control the sizes of blocking units of some other metal oxides and enhance their gas sensing performances.